Effect on anxiety of Coriandrum sativum leaf hydroethanolic extract oil and aqueous fraction in swiss albino mice - Puthallath, Rejeesh Edavan; Kotekar, Sridevi; Rao, S. N.; Narayana, Megha Rani; Nayak, Roopa P. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Anxiety is a protective reflex and the most common disorder. This study was done to evaluate the effect of anxiolytic property of oil and aqueous fractions isolated from hydroethanolic extracts of Coriandrum sativum leaf by novel freezing technique with swiss albino mice. Methods: Hydroethanolic extract of Coriandrum sativum leaves was prepared. Oil and aqueous part were separated with freezing technique. Animals were divided into six groups. Ist group served as control and 1% DMSO was administered orally. IInd to Vth group were administered with Coriandrum sativum oil fraction and Coriandrum sativum aqueous fraction at doses of 400 and 800 mg/kg orally. VIth group was treated with diazepam 1mg/kg orally. After one hour of dosing, battery of test was done viz, elevated plus maze (EPM), light dark arena, photo actometer and rotarod. Results: One-way analysis variance (ANOVA) followed by Dunnett’s multiple comparison test was used for statistical analysis. Anxiolytic property was found to be in the following order diazepam>coriandrum sativum aqueous 800>coriandrum sativum aqueous 400>coriandrum sativum oil 800>coriandrum sativum oil 400 mg/kg. All the extracts were devoid of adverse effects of motor coordination. Conclusions: Coriandrum sativum leaf possesses anxiolytic effect. The aqueous fraction of the hydroethanolic extract of the Coriandrum sativum leaf was found to be potent and further analysis may lead to identification of active compounds. The findings that the extract is non-sedating anxiolytic and is of good safety index are promising.